2000-2006 dönemi Türk vergi politikası - Buyun, Taylan Cihan (My University, 2008)
2000 - 2006 DÖNEMİ TÜRK VERGİ POLİTİKASI 3 bölümden oluşan bu tezin alışmalarından sonra gelen birinci bölümde 2000-2006 yılları arasındaki makro ekonomik gelişmeler anlatılarak söz konusu yıllara dair genel değerlendirmeye varılmıştır. Bunun yanı sıra yıllar sırasıyla ele alınarak büyüme, fiyat hareketleri ve enflasyon seyri, parasal büyüklükler ve para arzı açısından irdelenmiştir. İkinci bölümde 2000-2006 yılları arasında İMF’ye verilen Niyet Mektuplarında öngörülen vergi politikaları incelenerek 17, 18 ve 19. Stand-By düzenlemelerinde konu edilen Niyet Mektuplarının vergi politikası hedefleri anlatılmıştır. Üçüncü bölümde ise 2000-2006 döneminde vergi politikasındaki gelişmeler, vergi politikasında değişim dönemi, vergi mevzuatında yapılan düzenlemeler, Türk Vergi Sisteminin Avrupa Birliği Vergi Sistemi ile uyumu, vergi politikasında gerçekleşmeler incelenmiş ve Türk Vergi Sistemi üzerine genel bir değerlendirme yapılmıştır. Ayrıca 2000-2006 yılları arasındaki toplam vergi gelirleri ve vergi yükü dağılımı incelenmiş, 2013 vizyonuna göre vergi politikalarının temel amacı ve uygulama stratejilerine değinilmiştir. Ülkemizde iktisadi gelişme düzeyi düşük olan ülkeler grubundadır. Bu nedenle de yüksek harcama baskısı, vergi gelirlerinde yetersizlik ve özel tasarruflar düşük biçiminde özetlenebilir. Ancak, ülkemizde kamu gelirlerindeki yetersizliğin yanı sıra gelirlerdeki istikrarsızlıklar bütçe açısından büyük önem taşımakta ve vergilerdeki yavaş artış hızına oranla daha kötü sonuçlara yol açabilmektedir. Ülkemizde hem bütçe harcamalarının hem de vergilerin denetim ve disiplin altına alınmadığı görülmektedir. Bütçe açıklarının aşağı çekilebilmesi için, kamu harcamalarında etkenlik ve verimlilik denetiminin mutlaka yapılması, vergi denetim oranının mutlaka yükseltilmesi gerekir. TURKISH TAXATION POLICY BEHINDE 2000 - 2006 By explaining the macro economical developments between the years of 2000 and 2006, a general evaluation has been made for the mentioned years in the first section of this thesis, which contains 3 sections after the contents and the introduction works. It is also scrutinised within the angle of the growth, price movements and the inflation variance, the monetary magnitudes and the monetary supply within the sequence of the years. The taxation policies, which have been foreseen in the intention letters that have been issued to the IMF during the period of the years of 2000 and 2006, have been examined and the aims of the taxation policies of the intention letters, which were the subjects of the 17th, the 18th and the 19th Stand-By arrangements, have been explained in the second section. The developments in the taxation policies, the period of the change in the taxation policy, the arrangements that have been carried out in the taxation regulations, the conformity of the Turkish Taxation System with the European Union Taxation System, the realisations in the taxation policy have examined in the third section and an general evaluation have been made over the Turkish Taxation System. Additionally, the total tax income and the distribution of the taxation load have been examined between the years of 2000 and 2006 and it has been touched upon the basic aim of the taxation policies and the application strategies according to the 2013 vision. Our country is within the group of the countries, whose economical growth level is low. For this reason, it can be summarised as the high spending pressure, the deficiency in the tax incomes and the low private deposits. But, the instability in the incomes as well as the deficiencies in the public income have great importance for the budgetary issues and this can create worse results when compared to the slow growth of the taxes. It is seen in our country that both the budgetary spendings and the taxation are not audited and disciplined. In order to lower down the budgetary deficits, the efficiency and the productivity audits must definitely be carried out in the public spendings and the taxation auditing ratio must definitely be raised.
Keywords: Mali Politika; Vergilendirme_Türkiye